Considering the benefits of hosting refugees: Evidence of refugee camps influencing local labour market activity and economic welfare in Rwanda - Craig Loschmann; Özge Bilgili; Melissa Siegel (IZA Journal of Development and Migration, 2019)
This paper examines the influence of Congolese refugees on host communities in Rwanda, with a focus on labour market activity and economic welfare. The analysis takes advantage of newly collected survey data from three refugee camps and their surrounding areas to compare individuals and households within communities at various distances from, and therefore exposure to, the refugee population. We find evidence that residing close to a refugee camp makes it more likely that an individual is engaged in wage employment in comparison to farming or livestock production, representing a shift away from subsistence farming activities. In addition, there is evidence that females living nearby a camp have a higher occurrence of self-employment in business both as a primary and secondary activity, highlighting a notable gender-specific dynamic. Likewise, living in close proximity to a camp is associated with greater household asset ownership, benefiting both male- and female-headed households similarly, whereas no relationship is found in regard to ones' subjective perception of their household's economic situation. These generally encouraging results illustrate that refugees need not be a burden to their host societies, and their presence results in direct and indirect benefits.
Keywords: O12; F22; R23; J24; I31; J60; 330; Refugees; Host communities; Labour market; Assets; Rwanda